Codification Historical Astronomy Pre-Islamic Ancient Civilizations and Their Contributions to Islamic Astronomy - Era Zufialina; Muhammad Syahrul; Nailul Alvi Hidayah (AL - AFAQ : Jurnal Ilmu Falak dan Astronomi, 2024)
As one of the oldest branches of science, astronomy existed in the centuries before Christ and was pioneered by several ancient civilizations. After Islam came, Astronomy was used for religious purposes which became known as Astronomy. This article aims to explore the forms of astronomical knowledge in several ancient civilizations before Islam and then look at the connection and contribution of this astronomical knowledge to the development of Islamic astronomy. This research is library research using qualitative analysis techniques (content analysis and relationship analysis). From the studies and literature reviews carried out, it was found that astronomical knowledge in several ancient civilizations before Islam was simple astronomy and was used for various needs, such as worship (in this case worshiping the Gods), agriculture, animal husbandry, predicting fate, determining direction, and political needs. Among the forms of contribution of ancient civilizations before the Islamic Astrolomy can be seen in various things, including calendars, zij (ephemeris), or tools such as the Mizwalah which were modified and adapted to Islamic guidance by Muslim Astronomers. Ancient civilizations before Islam also gave birth to many great figures and thinkers, who had a lot of influence on the development of Islamic Astronomy.